Compatibilty study of thermoplastics in ron97 gasoline blended with ethanol - Amirul Syamin Mad Jeli, M. (Asian Research Publishing Network, 2016)
This paper investigates the compatibility of three types of thermoplastic: Low density polyethylene (LDPE), high density polyethylene (HDPE) and polypropylene (PP) with ethanol blended gasoline. These polymeric materials have been applied as components in automotive fuel system and the material integrity is important. The commercial RON97 unleaded gasoline were blended with 5, 10 and 20 vol. of ethanol to make the fuel blends. The plastic specimens were immersed in the fuel blend for 14 and 28 days at ambient conditions. Baseline tests using neat gasoline without ethanol were included for comparison purpose. The weight change, tensile strength and hardness properties were measured to assess the impact of the immersion tests. Results showed that the immersed specimens showed similar change of colour but no swelling was observed. Greater percentage of ethanol contributed to greater mass gain and incremental loss of tensile strength and hardness. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.